2020
DOI: 10.1001/jamasurg.2020.0093
|View full text |Cite
|
Sign up to set email alerts
|

Association Between American Board of Surgery Initial Certification and Risk of Receiving Severe Disciplinary Actions Against Medical Licenses

Abstract: IMPORTANCE Board certification is used as a marker of surgeon quality and professionalism. Although some research has linked certification in surgery to outcomes, more research is needed.OBJECTIVE To measure associations between surgeons obtaining American Board of Surgery (ABS) certification and examination performance with receiving future severe disciplinary actions against their medical licenses.DESIGN, SETTING, AND PARTICIPANTS Retrospective analysis of severe license action rates for surgeons who attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 15 publications
(59 reference statements)
4
32
0
Order By: Relevance
“…Thus, we propose that the mechanism for the associations we found is that physicians with greater medical knowledge and better medical judgement are, as a group, providing better care which results in improved outcomes, including decreased mortality. Our findings are concordant with other studies associating increased medical knowledge with better care as demonstrated by process measures, costs, state medical board disciplinary actions and specifically diagnostic knowledge as measured by MOC with emergency department visits, hospitalisations and death 8–10 15–18 21 32…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we propose that the mechanism for the associations we found is that physicians with greater medical knowledge and better medical judgement are, as a group, providing better care which results in improved outcomes, including decreased mortality. Our findings are concordant with other studies associating increased medical knowledge with better care as demonstrated by process measures, costs, state medical board disciplinary actions and specifically diagnostic knowledge as measured by MOC with emergency department visits, hospitalisations and death 8–10 15–18 21 32…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, there is reasonable evidence of a relationship with clinical care. For instance, there are several studies showing that certification is positively associated with the process of care provided to patients and their outcomes, while being negatively associated with disciplinary actions by state licensing boards 6–10. One aim of this study is to gather additional validity evidence based on the association between initial certification and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in the modular curriculum thus represents an effective learning strategy. Passing certification examinations is a marker of surgeon quality and professionalism, 26 and a curriculum that improves passage rates is an important contribution to surgical education and quality.…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative incidence plot shows the proportion of incidence of subjects with a particular condition over time. The curves presented in this graph disclose the behavior of the proportion of these subjects [ 21 ].…”
Section: Methodsmentioning
confidence: 99%